2016
DOI: 10.1111/1440-1681.12567
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T helper 9 cells and increased serum interleukin‐9 levels in patients with knee osteoarthritis

Abstract: The purpose of this study was to examine the roles of T helper 9 (Th9) cells and the serum interleukin (IL)-9 level in the pathogenesis of osteoarthritis (OA). The numbers of IL-9(+) CD4(+) CD8(-) T cells, interferon (IFN)-γ+ CD4(+) CD8(-) T cells, IL-4(+) CD4(+) CD8(-) T cells, and IL-17A(+) CD4(+) CD8(-) T cells in 25 OA patients and 13 healthy controls (HC) were examined by flow cytometry. The serum concentrations of IL-9, IL-4, IL-17A, and IFN-γ were also determined. The numbers of CD4(+) CD45RO(+) T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
0
23
1
Order By: Relevance
“…In patients with OA, the majority of CD4 + T cells in the synovial fluid and synovial tissue are CD45RO + and CD45RA − , suggesting that an accumulation of CD45RO + memory CD4 + T cells is a generalized phenomenon in OA joints (88). Similarly, a study with 25 OA patients and 13 healthy controls revealed that the number of circulating CD4 + CD45RO + T cells was significantly higher in patients with OA than in healthy controls (47). Other evidence for the possible involvement of Tm cells in the pathogenesis of OA includes the detection of the regulated on activation, normal T cell expressed, and secreted chemokine (a potent chemoattractant for leukocytes, such as CD45RO + memory T cells) and CD29 (a 1 integrin expressed by Tm cells) in the synovial fluid of OA patients (35, 37, 89).…”
Section: T Cells and Oamentioning
confidence: 98%
See 4 more Smart Citations
“…In patients with OA, the majority of CD4 + T cells in the synovial fluid and synovial tissue are CD45RO + and CD45RA − , suggesting that an accumulation of CD45RO + memory CD4 + T cells is a generalized phenomenon in OA joints (88). Similarly, a study with 25 OA patients and 13 healthy controls revealed that the number of circulating CD4 + CD45RO + T cells was significantly higher in patients with OA than in healthy controls (47). Other evidence for the possible involvement of Tm cells in the pathogenesis of OA includes the detection of the regulated on activation, normal T cell expressed, and secreted chemokine (a potent chemoattractant for leukocytes, such as CD45RO + memory T cells) and CD29 (a 1 integrin expressed by Tm cells) in the synovial fluid of OA patients (35, 37, 89).…”
Section: T Cells and Oamentioning
confidence: 98%
“…Similarly, no variation in either the percentage or the absolute number of circulating Th1 cells (CD4 + IFN-γ + T cells) has been found between patients with OA and healthy controls (46). However, in a study with 25 OA patients and 13 healthy controls, the number of circulating Th1 cells (IFN-γ + CD4 + CD8 − T cells) and the level of serum IFN-γ were found to be significantly higher in patients with OA than in healthy controls (47). The difference in the markers (CD4 + IFN-γ + vs. IFN-γ + CD4 + CD8 − ) used in the two studies to define Th1 cells may account for this discrepancy.…”
Section: T Cells and Oamentioning
confidence: 99%
See 3 more Smart Citations